A Proposed Framework for Implementing Kaizen in Saudi Public Education Schools in Light of Vision 2030 - Al-Enazi, Maryam Hamdan (Journal of Educational and Psychological Sciences, 2025)
This study aimed to present a proposed framework for implementing the Kaizen strategy in Saudi public education schools in light of Vision 2030. The study adopted a descriptive documentary analytical approach by analyzing literature and previous studies related to the research topic, to explore the reality of implementing the Kaizen strategy, the challenges it faces, and the requirements for its successful implementation. The study results revealed the current state of Kaizen strategy implementation in Saudi public schools, showing variations in both implementation levels and readiness. The results also indicated that the strategy implementation faces multiple challenges related to administrative and organizational aspects, human resources and training, as well as technical and material aspects. The study concluded that successful implementation of the Kaizen strategy requires comprehensive cultural and organizational change, with school leadership playing a pivotal role in this change through supporting and motivating staff. The findings also emphasized that continuous training and professional development are essential elements for the strategy’s success, while infrastructure and technology represent a major challenge that must be addressed. The study results also showed significant alignment between the Kaizen strategy and Vision 2030’s educational development goals. The study recommended adopting a comprehensive strategic plan for implementing Kaizen in schools, developing specialized training programs for school leaders and teachers, while providing the necessary infrastructure and technical support. It also suggested conducting future studies to evaluate the impact of implementing the Kaizen strategy on learning outcomes and improving the school environment and analyzing the relationship between Kaizen implementation and achieving Vision 2030 targets in the education sector.